One-step Barton decarboxylation by micellar catalysis – application to the synthesis of maleimide derivatives1. Issue 85 (16th September 2015) - Mangin, F.; Banaszak-Léonard, E.; Len, C.
<x xml:space="preserve">Abstract</x> Maleimides being studied or used in various applications, for the first time, a facile entry to Barton decarboxylation in aqueous media is described to obtain in one step substituted N-phenylmaleimide synthons.